Greece Financial Stumbling: Impact on the Global Economy - Ahuja, Deepika (IJRDO - Journal of Business Management, 2015)
This paper discusses the Eurozone crisis which took place in the year 2009-13 and the subsequent Greece’s alleged default on its debt obligations in June 2015 which made the fastest growing economies lethargic. With the possible exit of Greece from Eurozone, adverse consequences for member countries might be manifold. So, we have tried to incorporate the impact of Greece debt crisis on different developing economies of the world. In the end, the paper attempts to suggest the steps to revive the world economic system and the possible solutions for Greece.